Procedures for successful data collection through psychological tests in the elderly - Diniz, António Moreira (2016)
This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License which permits unrestricted non-commercial use, distribution, and reproduction in any medium provided the original work is properly cited.